Each baby counts in 2018 – lessons learned and future directions. Issue 8 (August 2018) - Robertson, Louise; Knight, Hannah; Prosser-Snelling, Ed; Petch, Emily; Knight, Marian; Cameron, Alan; Alfirevic, Zarko
Abstract: The Royal College of Obstetricians and Gynaecologists (RCOG) launched the Each Baby Counts (EBC) project in 2015. The aim of the project is to reduce the number of stillbirths, early neonatal deaths and severe brain injuries in term babies born following labour by 50% by the year 2020. The first full report focussed on the quality of local reviews, fetal monitoring, individual human factors and neonatal care. For this article we have not focussed on the neonatal issues but have summarized the main points from each chapter. The aim of EBC will be achieved by focusing on three themes: (i) improving the quality of reviews of these babies, prompting local units to address their systematic failings that led to the outcome; (ii) development of toolkits and resources to support units to implement the recommendations in the report; (iii) improving care by establishing a platform for shared learning between units in order to adopt a more proactive approach to reducing babies who are harmed during labour.